SHOULD WE DISCARD THE INCOME CONCEPT? - Moonitz, Maurice (The Accounting Review, 1962)
Ever since the rise to prominence of the income statement in the late twenties and early thirties, the underlying concept of business or accounting income has been the subject of searching analysis and criticism. There has been a type of criticism which seems to accept the objectives of profit measurement but which asserts that accounting is not doing the best job of which it is capable. A growing disillusionment can be detected with respect to the validity and significance of calculations of periodic net profit. Firstly the rules for the realization of revenue and of profit are too narrow and restrictive. Secondly some of the classifications employed in accounting, like distinction between fixed and variable costs, are inappropriate. Thirdly more attention should be paid to statements of the source and application funds as the scope of reporting procedures is too narrow. Further a second major type of criticism centers on the income concept itself by asserting that income is ultimately a matter of the expectations of individuals. As a consequence, the inference is drawn that the measurement of these subjective expectations is impossible by any means known to accounting or to economics.